2004
DOI: 10.1300/j001v22n01_10
|View full text |Cite
|
Sign up to set email alerts
|

Models of Supervision

Abstract: Prevailing models of clinical supervision are discussed and evaluated within the context of training psychologists for the school setting, with the goal effectiveness of developing a professional identity. Contextual variables (e.g., university versus field-based training), level of training, and interpersonal and intrapersonal characteristics are examined as contributory factors in the supervisory enterprise. A model emerging from Erikson's developmental theory is posited as an umbrella perspective for all mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 25 publications
2
5
0
Order By: Relevance
“…A relationship enhances the supervisor's ability to adjust his or her supervision to each learner's supervision needs . For example, with a strong relationship, the trainee can feel more comfortable in seeking help, receiving feedback and incorporating changes . We found that perceptions of a strong resident–supervisor relationship seemed to enable the delivery of more specific feedback that provided more precise guidance for the resident's development, as has been identified previously …”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…A relationship enhances the supervisor's ability to adjust his or her supervision to each learner's supervision needs . For example, with a strong relationship, the trainee can feel more comfortable in seeking help, receiving feedback and incorporating changes . We found that perceptions of a strong resident–supervisor relationship seemed to enable the delivery of more specific feedback that provided more precise guidance for the resident's development, as has been identified previously …”
Section: Discussionsupporting
confidence: 64%
“…27 For example, with a strong relationship, the trainee can feel more comfortable in seeking help, receiving feedback and incorporating changes. 28 We found that perceptions of a strong resident-supervisor relationship seemed to enable the delivery of more specific feedback that provided more precise guidance for the resident's development, as has been identified previously. 29 Our findings illustrate how the development of trust can be understood as a process that progresses from a starting point through to outcomes, although starting points, influencing factors and outcomes vary among supervisors.…”
Section: Discussionsupporting
confidence: 58%
“…Second, school psychologists take on multiple professional roles (National Association of School Psychologists, , highlights 10 professional practice domains), making school psychologists’ practice arguably broader than the practice of many other professionals focused primarily on a single practice area (e.g., a counseling psychologist or psychotherapist who predominately provides individual or group counseling; Kaufman & Schwartz, ). Competent supervision requires knowledge of supervision praxis as well as content areas being supervised (American Psychological Association, ; Falender, ), and supervisors of school psychologists require a wide breadth of knowledge and skills to support supervisee development.…”
Section: Issues In Generalizing Psychology Supervision Research To Scmentioning
confidence: 99%
“…Newman et al () emphasized the importance of intentionality in supervision rooted in an organizational framework. Developmental approaches were highlighted by Kaufman and Schwartz () to be the most potentially relevant lens to consider supervision in school psychology.…”
Section: Topics With Limited Coverage In the Literaturementioning
confidence: 99%
“…As a clinical supervisor, I feel that I have an obligation to impart the knowledge I have gained from my mentors and to share my struggles and not-so-glorious moments with my supervisees to facilitate open discussions about their experiences as a budding psychologist of color. In addition, I see supervision as a place to learn and think about relationships, interplay between culture and clinical issues, and topics related to professional growth (Kaufman & Schwartz, 2003). My hope is that this process of reflection and self-exploration in supervision will help each supervisee to become a strong professional, whose cultural values and beliefs are reflected in her work so she will be able to carry on the cycle of mentorship to the generation that follows.…”
Section: Chiaki Sasaki Psydmentioning
confidence: 99%